Sustainability assessment of mangrove forest as a tourist destination: A case study using GSTC Criteria in Kota Belud, Sabah, Malaysia - Hamimah Talib; N Nurul Huda; Kamlisa Uni Kamlun; Rosmalina Abdul Rashid; Chan, Jennifer Kim Lian (IOP Publishing Ltd, 2022)
The mangrove forest has been one of the natural areas that provides the local communities with economics opportunities especially those involving tourism activities. However, over time it could face destruction if there is no measure taken to monitor the impacts. The objective of this study is to identify mangrove forest conservation efforts in Nanamun River, Kota Belud, Sabah, Malaysia as sustainable ecotourism destination and to propose sustainable conservation guidelines based on the Global Sustainable Tourism Council's Criteria and Indicator (GSTC) guidelines. A total of 14 in-depth interviews were conducted with stakeholders which involved the local government authorities, community representatives and local tour operators, as the primary data for this study. Purposive sampling were deployed specifically snowball sampling technique to identify key persons that could provide relevant information. The data collecting instrument were based on the Global Sustainable Tourism Council Criteria and Indicator (GSTC) guidelines for destination management which comprised 4 main sections (criterias): A) Demonstrate effective sustainable management; B) Maximize economic benefits to the host community and minimize negative impacts; C) Maximize benefits to communities, visitors, and culture; minimize negative impacts; and D) Maximize benefits to the environment and minimize negative impacts. This study found that there are some efforts to conserve mangrove forest in the study area. Among the 4 criteria, section A (sustainable management) and B (economic benefits) were found to have most of the indicators for sustainability checked. However, some of the conservation efforts might still need to be formalized. Recommendations were made in accordance with the gaps found based on the GSTC guidelines used.